Divinely masculine: Neopaganism and gender identity in contemporary America - Enberg, Jessica M., author; Snodgrass, Jeffrey G., advisor; Margolf, Diane Claire, committee member; Browne, Katherine E., 1953-, committee member; Pickering, Kathleen Ann, 1958-, committee member (Colorado State University. Libraries, 2010)
This research is focused on how men use religion to define their gender identity. Specifically, this paper looks at the religion Neopaganism. Out of the 1960s and 1970s Counter Cultural and New Religious Movements rose Neopaganism, an earth-based religion in which the Goddess(es) and the God(s) are venerated, nature's yearly cycle of seasons are celebrated, and magic is practiced. This paper will discuss how the Feminist and Men's Movement that arose from the 1960s and 1970s affected gender roles in the U.S. and prompted the study of U.S. Masculinities. From these studies it was determined that men's gendered identities could no longer be understood in terms of a singular masculinity, but as several masculinities. These masculinities are placed into two categories: the hegemonic masculinity, or the ascendant and dominant masculinity in the U.S. culture, and subordinate masculinities, which are those that differ from the hegemonic masculinity in terms of ethnicity, sexuality, religion, class position and marital status. The focus of this paper is how men in Neopaganism use religion to define their subordinate masculinities. The research group for this study consisted of five men and four women, with the main focus on the male informants. The ethnographic methodologies included observation, participation, and 36 in-depth, open-ended interviews. The main findings include the following: the male informants have what they consider to be strong feminine sides; while the male informants acknowledged there is a U.S. male stereotype they do not believe in a strict gender role for men and women; all the male informants were looking for balance of masculine and feminine in their lives; the balance they sought had more meaning for them when found through religion because it offered divine justification for how they perceived themselves as men; and the Neopagan environment in which they participate offers both a safe haven for them to express their true gender identity without fear, retribution, ridicule or judgment.